Effects of phosphate solubilizers and biochar on growth and yield of tomato (Solanum lycopersicum) - Asilah Abdul Mutalib (Tanjong Malim, 2019)
Effects of phosphate solubilizers and biochar on growth and yield of tomato (Solanum lycopersicum) by Asilah Abdul Mutalib